COVID-19 Resurgence in 2025: India’s Continuing Public Health Challenge - Satish Kumar Sarankar; Sushma Somkuwar (International Journal of Tropical Medicines, 2025)
The year 2025 has witnessed the resurgence of COVID-19, reigniting concerns at both global and national levels regarding the persistent threat posed by SARS-CoV-2. In early 2025, India witnessed a moderate resurgence of COVID‑19, characterized by the emergence of Omicron sub-variants and a rise in mild-to-moderate infections. As of mid-June, active COVID‑19 cases in India totaled approximately 6,000–7,400, with hotspots in Kerala (~2,100 cases), Delhi (~600), Maharashtra (~500), and several other states. The Indian SARS-CoV-2 Genomics Consortium (INSACOG) has identified key sub-lineages including JN.1, LF.7, NB.1.8.1, and recently XFG. These variants are associated with immune evasion and increased transmissibility, though current data indicate cases remain predominantly mild, with low hospitalization and death rates. India’s diagnostic efforts include scaling next-generation RT-PCR, antigen testing, and expanded genomic sequencing. Therapeutic protocols adhere to WHO recommendations, incorporating antivirals, immunomodulators, and oxygen therapy. Most cases are managed on an outpatient basis due to limited severity. India’s vaccination campaign, totaling over 2.4 billion doses, has encountered booster gaps. Variants under monitoring have prompted targeted booster drives, especially for high-risk groups. Fresh public health measures, mask advisories, reinforced surveillance, and state-led containment efforts aim to curb further spread. This review provides a detailed assessment of the evolving COVID-19 situation in India, outlining current challenges, national response efforts, and future directions to mitigate the ongoing health crisis.
Keywords: COVID-19 India 2025; COVID-19 Resurgence; India's Vaccine Development; Omicron Sub-lineages 2025; Pandemic Preparedness India; Pandemic Resilience India